Hubungan Konsep Diri dengan Perencanaan Karir Peserta Didik di SMK Negeri 1 Gunungsitoli - Laoli, Jonisman Kristian; Lugu, Windi Wulandari (Lembaga Intelektual Muda (LIM) Maluku, 2023)
The purpose of the study was to determine the positive and significant relationship between self-concept and career planning of students at SMK Negeri 1 Gunungsitoli. This research is quantitative research with data collection techniques using observation techniques and questionnaires. The data was analyzed by parametric statistical methods i.e., multiple regression analysis with the help of the SPSS program. The sample number is 30 students and sampling is carried out randomly with cluster random sampling technique. Based on data analysis, the results of the t-test analysis are known that there is a positive and significant influence between self-concept variables and career planning variables. With a t-test calculation result of 14.454. While the table is 1.701 at a significant level of 5%, which means that there is a positive influence and significance between a variable of self-concept (X) and a variability of career planning (Y) class XI Fashion Design SMK Negeri 1 Gunungsitoli